HUBUNGAN BEBAN KERJA TERHADAP MEKANISME KOPING PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT JIWA - Reggiana Sarastya; Jumaini Jumaini; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Adaptive coping mechanism is needed by nurses in dealing with workload, so nurses can provide good service to patients and families. The aim of this research is to determine the correlation of Nurse’s Workload to Coping Mechanisms inpatient care at Tampan Mental Institution Riau Province. This research was using descriptive correlational design with cross sectional approach. The number of sample was 48 nurses in wards taken with using total sampling technique. The instrument of this research was questionnaire with 25 statement of workload and 15 statement of coping mechanisms. Analysis used were univariate analysis to determine the frequency distribution and bivariate analysis using chi square. The result of the research shows that respondent that had a hard workload do the adaptive coping mechanism as manya as 15 people (65,2%), and the respondent that had hard workload do the maladaptive coping mechanism as many as 8 people (34,8%) while the respondent that had a light workload do the adaptive coping mechanism as many as 10 people (40%) and respondent who had a light workload do the maladaptive coping mechanism as manya as 15 people (60%). The statistical results showed p value (0,145) > α (0,05), it can be concluded that there is no correlation between nurses workload and coping mechanisms of nurse inpatient care in Tampan Mental Institution Riau Province. Even though there is no correlation, it is hoped that the Mental Institution can manage the workload in accordance with the rules that have been determined, so that the nurse is maximal in providing nursing services.   Keywords: Coping mechanisms, mental institution, workload of nurses